Salt chemistry effects on salinity assessment in the Arkansas River Basin, Colorado - Cooper, Curtis Allen, author; Cardon, G. E. (Grant Edmund), author; Davis, Jessica, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2006)
Calibration equations developed in this research, use either depth averaged or depth weighted salt concentrations and/or predicted pore water salt concentrations from Visual Minteq. For example, the current Downstream sub-region calibration equation relating EM readings to soil ECe has an R2 of 0.54 with an root mean square error (RMSE) of 2.16 dS m-1. The equation from this research, using depth weighted Mg concentrations and SAR with Visual Minteq has an R2 of 0.93 with a RMSE of 1.34 dS m-1, and is effective for both the Upstream and Downstream sub-regions. Validation of these equations suggests that predictability is equivalent between the initial sub-region model and the models for the entire region. The inclusion of the chemistry/mineralogy in the calibration equations serves to resolve some of the unevenness of the EMv-ECe calibration, but at the cost of more complex computing and data requirements. However, the inclusion of the chemical data offers an alternate approach not yet utilized in extrapolating the calibration of the EM-38 from a field to a regional scale.
Completion Report 206.
March 2006.
Keywords: Salinity -- Arkansas River Watershed; Soils, Salts in -- Arkansas River Watershed; Watershed management -- Arkansas River Valley; Water-supply, Agricultural -- Arkansas River Watershed; Environmental monitoring -- Arkansas River Watershed; Arkansas River Valley